Pengaruh Kemudahan Bertransaksi dan Kualitas Layanan E-Commerce Terhadap Keputusan Pembelian di Kota Batam - Dhea Kiran Euunike; Wasiman, Wasiman (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study was conducted to systematically explore the influence of the level of ease of transactions and the quality of e-commerce services on the process of determining consumer purchasing decisions in Batam City. The research framework was built with a descriptive-oriented quantitative approach through the involvement of 100 respondents who actively utilize digital transaction services, which were determined using a purposive sampling technique based on the Lemeshow formulation to ensure the adequacy and representativeness of the sample. Empirical data were collected through a structured questionnaire and then processed using statistical analysis stages that included testing the validity and reliability of the instrument, evaluation of classical assumptions, multiple linear regression modeling, and verification of hypotheses through t-tests and F-tests. The results of data processing revealed that the variable of ease of transactions contributed 18.8% to purchasing decisions, while service quality contributed an influence of 63.5%. The coefficient of determination (R²) reaching 73.3% indicates that both independent variables simultaneously have substantial explanatory power towards variations in consumer purchasing behavior. Both partial and simultaneous testing confirmed a significant influence, thus confirming that simplifying transaction mechanisms and strengthening digital service quality are strategic determinants in driving e-commerce consumer purchasing decisions in Batam City.